Severe Hyponatremia as the Initial Sign Preceding Guillain-Barré Syndrome, an Acute Inflammatory Demyelinating Polyneuropathy: A Case Report - Benjamin Kloesel; LaTonya J. Hickson (Case Reports in Neurological Medicine)
Guillain-Barré syndrome is an immune-mediated polyneuropathy that frequently presents with progressive muscle weakness. Hyponatremia has recently been described as a feature of this condition, generally appearing over the course of the illness and following the diagnosis of this demyelinating process. We report a case of Guillain-Barré syndrome presenting with severe hyponatremia that is further exacerbated by intravenous immune globulin therapy. Awareness should be raised for consideration of both Guillain-Barré syndrome and its treatment with intravenous immune globulin therapy as the cause of hyponatremia.